Cloning, heterologous expression, and characterization of a novel thioesterase from natural sample - Suharti (Heliyon, 2021)
A novel thioesterse gene was successfully cloned and sequenced directly from natural sample of Domas Hot Spring, West Java, Indonesia. Homological analysis of the sequence showed that the gene appeared high homology to thioesterase genes with the highest to a putative thioesterase gene from uncultured Acidilobus sp. JCHS at 66% identity. However, phylogenetic analysis showed that the protein was separated from the branch with other known thioesterases. The size of the gene is around 500 base pairs, lied into 2 kb DNA fragment from a random PCR amplicon. The gene was overexpressed in Escherichia coli, a dominant band appeared at 17 kDa in SDS-PAGE with expression level at around 32% of total proteins. The activity of the purified protein using acetyl-CoA as substrate showed that the protein exhibited thioesterase activity. Furthermore, the enzyme also showed esterase activity on p-nitrophenyl ester as substrate. Detail characterization of esterolytic activity showed that the enzyme preferred p-nitrophenyl decanoate as substrate. The optimum activity of the enzyme was at 80 °C and pH 8. Activity of the enzyme was maintained after incubation at 80 °C up to 24 h. In addition, the enzyme was favorable on polar organic solvents. All the data obtained suggested that the enzyme is a novel alkaline thermostable thioesterase.